Interactive Learning Multimedia to Increase Student Motivation in Science Learning on the Photosynthesis Topic for Grade IV Elementary School - Maritza Agustin; I Made Citra Wibawa; Wayan Eka Paramartha (Universitas Pendidikan Ganesha, 2025)
The problem addressed in this study is the low learning motivation of students in IPAS (Science) learning, particularly on the topic of photosynthesis in Grade IV of elementary school. This study aims to: (1) produce a design of interactive learning multimedia based on Canva; (2) determine its validity; (3) test its practicality; and (4) test its effectiveness. This is a development research using the ADDIE model and employing a one-group pretest-posttest design. The instruments used were questionnaires with a rating scale, and the data were analyzed using descriptive quantitative and qualitative methods. The subject of this research was interactive learning multimedia, involving 1 teacher and 20 Grade IV elementary school students as participants. The results showed that: (1) the multimedia was successfully designed using Canva, (2) the validity test received high scores from media experts (0.944) and material experts (0.962), (3) the practicality test obtained very good scores from the teacher (99%) and students (92%), and (4) the effectiveness test showed a significance value of 0.000 < 0.05. Therefore, the developed interactive learning multimedia is considered valid, practical, and effective in increasing students' learning motivation. The implication of this research is that the media can serve as an innovative alternative in IPAS learning, especially for the topic of photosynthesis, to create a more engaging and motivating learning process.